2022
DOI: 10.1002/adhm.202202691
|View full text |Cite
|
Sign up to set email alerts
|

The Epitope Basis of Embryonic Stem Cell‐Induced Antitumor Immunity against Bladder Cancer

Abstract: Embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) share many cellular and molecular features with cancer cells. Taking advantage of these similarities, stem cells are effective vaccines against cancers in animal models. However, the molecular basis is not well understood, which hinders the development of effective cancer vaccines. Here, prophylactic and therapeutic bladder cancer vaccines composed of allogeneic ESCs and CpG with or without granulocyte macrophage colony stimulating factor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…We showed that OMV-P significantly decreased tumor size in both the bladder cancer and lung cancer models. In agreement with the results from our previous research [ 1 ], the flow cytometry analysis revealed elevated ratios of CD8 + effector T cells, CD4 + memory T cells, and CD8. + memory T cells in OMV-P-treated mice, which suggests ESC-based epitopes have the potential to inhibit different types of tumor growth via inducing antitumor T cell responses.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We showed that OMV-P significantly decreased tumor size in both the bladder cancer and lung cancer models. In agreement with the results from our previous research [ 1 ], the flow cytometry analysis revealed elevated ratios of CD8 + effector T cells, CD4 + memory T cells, and CD8. + memory T cells in OMV-P-treated mice, which suggests ESC-based epitopes have the potential to inhibit different types of tumor growth via inducing antitumor T cell responses.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, a wide range of vaccines based on ESCs-derived oncofetal antigens are being tested in pre-clinical studies for their potential in inhibiting tumor growth [ 32 34 ], while some single-epitope vaccines have already reached stage I/II clinical trials [ 35 ]. In our previous study, we reported that TAAs shared by both ESCs and tumor cells could potently trigger an immune response against bladder cancer [ 1 ]. However, peptide-based vaccines have issues of short half-life of peptides and short-lived antitumor immune response in vivo [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations